Word order in job interviews: the Malaysian perspective / Selvajothi Ramalingam ... [et al.] - Ramalingam, Selvajothi; Krishnan, Isai Amutan; Suppiah, Puspalata C.; Maruthai, Elanttamil (Universiti Teknologi MARA, 2020)
The present study was conducted to analyse the use of word order in job interviews. The data was collected from participants in an organisation in Kuala Lumpur, Malaysia. Ten candidates of different races between the ages of 23 and 25 participated in the study. Radford’s syntactic theory of word order was employed to qualitatively analyse the data. It was found that positive sentences were predominantly used by the selected (n = 10; 47.4%) compared to the not selected (n = 10; 44.0%) and keep in view (KIV) (n = 23; 39.0%) job candidates. The findings further revealed that the types of word order used in utterances by the selected candidates were different compared to those who were not chosen for interviews. Selected candidates used more negative sentences, subordinate clauses, and time expression in sentences, whereas those who were not selected utilised adverbs of manner in negative sentences, subordinate clauses, and time expression in sentences, while the not selected candidates only used the position of adverbs. On the other hand, the KIV candidates used positive sentences, subordinate clauses and word order in questions in their utterances. The study can provide important contributions to knowledge on the use of English when developing employment course modules emphasising word order as an essential element in portraying good English language proficiency in job interviews.